2018
DOI: 10.1039/c8tx00062j
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular mechanisms of sulfur mustard toxicity on spermatozoa and male fertility

Abstract: Sulfur mustard (SM) is a toxic compound that can target human spermatozoa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…In this context, the capacity of melatonin to modulate the inflammation-immune axis (48,49) should mitigate the pathological features induced by sulfur mustard through the modulation of the inflammation-immune axis. Some studies have suggested that the enhancement of oxidative species production or weakening of antioxidant mechanisms are crucial in the acute toxicity of sulfur mustard and long-term effects following acute poisoning (22,38,(50)(51)(52)(53). The powerful nitrosating agent peroxynitrite (ONOO • ) is involved in detrimental effects of all mustards as it covalently modifies all the principal types of biomolecules including membrane lipids, thiols, proteins and purine and pyrimidine bases (54)(55)(56).…”
Section: Immune-inflammation and Oxidative Stress Induced By Vesicantmentioning
confidence: 99%
“…In this context, the capacity of melatonin to modulate the inflammation-immune axis (48,49) should mitigate the pathological features induced by sulfur mustard through the modulation of the inflammation-immune axis. Some studies have suggested that the enhancement of oxidative species production or weakening of antioxidant mechanisms are crucial in the acute toxicity of sulfur mustard and long-term effects following acute poisoning (22,38,(50)(51)(52)(53). The powerful nitrosating agent peroxynitrite (ONOO • ) is involved in detrimental effects of all mustards as it covalently modifies all the principal types of biomolecules including membrane lipids, thiols, proteins and purine and pyrimidine bases (54)(55)(56).…”
Section: Immune-inflammation and Oxidative Stress Induced By Vesicantmentioning
confidence: 99%
“…The use of the progressive motility of animal-derived spermatozoa as a method to identify the toxic effects of substances has been previously implemented [18][19][20]. The toxic effects by substances on human spermatozoa motility have been likewise reported [21][22][23][24]. However, the availability of robust human motility test systems that allow for a broad and serial substance evaluation for putative toxic effects on mitochondrial function is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some studies have shown that SM can disrupt sex hormones, and induce a variety of structural and functional disorders in the male reproductive system post exposure. 18 19 How these changes affect fertility among those who survived SM exposure is, however, still unclear. 19–21 Moreover, in a study among SM survivors (males and females) almost 15 years after exposure to SM, no increased infertility was observed.…”
Section: Introductionmentioning
confidence: 99%